Reduced Retinal Thickness Predicts Age-Related Changes in Cognitive Function - Mammadova, Najiba; Neppl, Tricia K.; Denburg, Natalie L.; West Greenlee, M. Heather (Frontiers in Aging Neuroscience, 2020)
Currently, there is a lack of biomarkers to identify individuals in the early stages of Alzheimer’s disease (AD). A preponderance of evidence suggests that neurodegenerative processes that affect the brain, may also affect the retina. Using optical coherence tomography (OCT), a non-invasive approach, many have shown thinning of the retina in Alzheimer’s disease and the developmental precursor to AD, mild cognitive impairment (MCI). However, the relationship between retinal thickness and cognitive function is not entirely clear. This is likely due to the disparity in diagnostic criteria used to determine MCI that does not fully probe the cognitive domains that are particularly vulnerable to aging. This study used a comprehensive neuropsychological assessment involving multiple domains of cognition to determine if retinal thickness correlates with cognitive performance in a normal aged population. In this study, 20 healthy individuals between 60 and 90 years of age were administered neuropsychological instruments probing various domains of cognitive function, and optical coherence tomography to measure peripapillary retinal nerve fiber layer (RNFL) thickness. We found that RNFL thickness is correlated with neuropsychological performance in multiple cognitive domains (e.g., attention/concentration, psychomotor speed and executive function). Our work demonstrates a positive correlation between RNFL thickness and several, but not all, domains of cognitive function in a normative aging population. By determining which cognitive domains retinal thickness can predict, this work can help identify individuals at risk or in preclinical stages of AD and other neurodegenerative diseases.